Annual Plan 2004-05 Volume I ( Part-1) Government of Uttar Pradesh - Planning Commission (Planning Commission, 2004)
The most important and unique economic indicator which throws light on the effectiveness and impact of different developmental programmes being implemented in various sectors is income level of a State. The statistics of state income depict that annual growth rate of total income in the Ninth Five Year Plan period (1997-2002) in U.P. was 2.3% as against 5.5 % in India. Similarly, annual growth rate of per capita income in the same period for U.P. was 0.0% as against 3.6% of India. Comparative growth rates in income from First to Ninth Five-Year Plan is given in Annexure-7. The state’s contribution in National Income according to quick estimates for 2002-03 was 8.3 % which was almost equal to the figure of provisional estimates for 2001-02 (8.6%) and the figure (8.7%) of estimates for 2000-01.
Government of Uttar Pradesh State Planning Commission
Government of Uttar Pradesh State Planning Commission